Management of traumatic extradural haematoma at tertiary referral centre: a prospective study - Laxmanrao, Kankal Ashutosh; Dileep, Rai Prachi (International Surgery Journal, 2026)
Background: Extra dural haematoma (EDH) means collection of blood between skull and dura mater due to bleeding from extra-cerebral vessel which is a common complication of head injury, often fatal if not treated intime and can be managed by both conservatively and surgically, decision has made individually in each case depending on patient’s age, hematoma size, location, patient’s neurological status and course. Present study was done to study different ways of management of EDH and their prognostic outcomes and to predict outcome of conservative against surgical intervention at tertiary care centre. Methods: Present prospective study was conducted in Surgery department at tertiary care centre for 2 years and 100 subjects included in study. Data was collected about wound mechanism, clinical features, occupation, Glassgow Coma score and thorough evaluation for evidence of traumatic sequelae. Data collected and entered in Microsoft excel, statistics were estimated by chi square test p<0.005 considered as significant. Ethical clearance was obtained. Results: Out of 100 participants, 53% participants belong to age group 21-40 years with M:F ratio was 4.26:1.22% study participants students followed by drivers 17%. Most common mechanism of trauma was RTA (61%) and GCS score in range of 13-15 contributing 61%. The 88 study subjects managed conservatively whereas 12 cases were managed surgically. Mortality rate 8.33% in operative mode whereas 1.34% in conservative mode of management. Conclusions: Present study concluded that when surgical treatment is indicated that time early surgical intervention is associated with the best prognosis. Many factors affect outcome of EDH surgery and most important is duration of time between incident/accident and operation in neurosurgical operation.